Gaps in hepatocellular carcinoma surveillance among insured patients with hepatitis B infection without cirrhosis in the United States. Issue 12 (30th September 2022) - Nguyen, Mindie H.; Roberts, Lewis R.; Engel‐Nitz, Nicole M.; Bancroft, Tim; Ozbay, A. Burak; Singal, Amit G.
Abstract: Suboptimal adherence to guidelines for hepatocellular carcinoma (HCC) surveillance among high‐risk patients is a persistent problem with substantial detriment to patient outcomes. While patients cite cost as a barrier to surveillance receipt, the financial burden they experience due to surveillance has not been examined. We conducted a retrospective administrative claims study to assess HCC surveillance use and associated costs in a US cohort of insured patients without cirrhosis but with hepatitis B virus (HBV) infection, monitored in routine clinical practice. Of 6831 patients (1122 on antiviral treatment, 5709 untreated), only 39.3% and 51.3% had received any abdominal imaging after 6 and 12 months, respectively, and patients were up to date with HCC surveillance guidelines for only 28% of the follow‐up time. Completion of surveillance was substantially higher at 6 and 12 months among treated patients (51.7% and 69.6%, respectively) compared with untreated patients (36.9% and 47.6%, respectively) ( p  < 0.001). In adjusted models, treated patients were more likely than untreated patients to receive surveillance (hazard ratio [HR] 1.75, 95% confidence interval [CI] 1.53–2.01, p  < 0.001), and the proportion of those up to date with surveillance was 9.7% higher (95% CI 6.26–13.07, p  < 0.001). Mean total and patient‐paid daily surveillance‐related costs ranged from $99 (ultrasound) to $334 (magnetic resonance imaging), and mean annual patient costs due to lost productivity for surveillance‐related outpatient visits ranged from $93 (using the federal minimum wage) to $321 (using the Bureau of Labor Statistics wage). Conclusion : Use of current HCC surveillance strategies was low across patients with HBV infection, and surveillance was associated with substantial patient financial burden. These data highlight an urgent need for accessible and easy‐to‐implement surveillance strategies with sufficient sensitivity and specificity for early HCC detection.